2018
DOI: 10.1192/bjp.2018.196
|View full text |Cite
|
Sign up to set email alerts
|

Repeated oral ketamine for out-patient treatment of resistant depression: randomised, double-blind, placebo-controlled, proof-of-concept study

Abstract: BackgroundKetamine has been demonstrated to improve depressive symptoms.AimsEvaluation of efficacy, safety and feasibility of repeated oral ketamine for out-patients with treatment-resistant depression (TRD).MethodIn a randomised, double-blind, placebo-controlled, proof-of-concept trial, 41 participants received either 1 mg/kg oral ketamine or placebo thrice weekly for 21 days (ClinicalTrials.gov Identifier: NCT02037503). Evaluation was performed at baseline, 40 and 240 min post administration and on days 3, 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 27 publications
(92 reference statements)
0
50
0
Order By: Relevance
“…Pooled data revealed a significant benefit of ketamine over placebo also in terms of response and remission, after exclusion of the study involving heavily pretreated patients with suicidal thoughts [30], due the reasons described below. As reported in included RCTs, antidepressant effects were maintained for about 1 week of follow-up after ketamine cessation [31,32]. Although data from uncontrolled studies showed that most patients relapse after a few weeks (usually before the end of the third week) after cessation of even repeated ketamine treatment [12,13,15], a very recent RCT on intranasal esketamine showed a sustained improvement in the mean MADRS ratings over the 8-week follow-up after treatment cessation [16].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Pooled data revealed a significant benefit of ketamine over placebo also in terms of response and remission, after exclusion of the study involving heavily pretreated patients with suicidal thoughts [30], due the reasons described below. As reported in included RCTs, antidepressant effects were maintained for about 1 week of follow-up after ketamine cessation [31,32]. Although data from uncontrolled studies showed that most patients relapse after a few weeks (usually before the end of the third week) after cessation of even repeated ketamine treatment [12,13,15], a very recent RCT on intranasal esketamine showed a sustained improvement in the mean MADRS ratings over the 8-week follow-up after treatment cessation [16].…”
Section: Discussionmentioning
confidence: 89%
“…Two of the RCTs investigating repeated ketamine administration used oral ketamine, and both of them confirmed that this route of administration was highly effective in amelioration of depressive symptoms at 2-3 weeks [31,33]. Oral dosing of ketamine is a recognized route of administration in chronic pain management [56] and would be a more practical and acceptable delivery method than Fig.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Ketamine, a glutamatergic modulator and a rapidly acting antidepressant (aan het Rot et al, 2010;Berman et al, 2000;Domany et al, 2018;Murrough et al, 2013;Singh et al, 2016;Zarate et al, 2006), has been shown to rapidly reduce suicidal ideation (Grunebaum et al, 2018;Ibrahim et al, 2011;Price, Nock, Charney, & Mathew, 2009). In addition, esketamine, the S enantiomer of racemic ketamine, has shown similar results (Canuso et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Only five recent human studies included a control group 9,[55][56][57][58] , and, strikingly, they showed contradictory results. Ketamine either maintained antidepressant efficacy 9,56,57 or failed to outperform placebo 58 and was ineffective 55 , additionally causing side effects 55,58 . The study of Canuso et al 56 demonstrated that although the depressive symptoms diminish after ketamine at all time points, the suicidal ideation reduces only at 4 h, and displays no improvement at 24 h or at end-point day 25.…”
Section: Effects Of Repeated Ketamine Vs Placebomentioning
confidence: 99%